2022
DOI: 10.3847/1538-4357/ac7da6
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Electron Heating in Turbulence-driven Magnetic Reconnection in the Near-Sun Solar Wind

Abstract: We perform a high-resolution, 2D, fully kinetic numerical simulation of a turbulent plasma system with observation-driven conditions, in order to investigate the interplay between turbulence, magnetic reconnection, and particle heating from ion to subelectron scales in the near-Sun solar wind. We find that the power spectra of the turbulent plasma and electromagnetic fluctuations show multiple power-law intervals down to scales smaller than the electron gyroradius. Magnetic reconnection is observed to occur in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 121 publications
1
3
0
Order By: Relevance
“…The contribution by E || (Figure 6b) has a slight decreasing trend over time, where the median value is above 50% at the early time and below 50% later. The dominant role of E || energization is consistent with recent observations in magnetosheath turbulence where the pdf of the work done by E || to electrons is found (Xu et al, 2023), and kinetic simulations of turbulence where T e|| enhancements are found to be significant around the reconnection onset (Franci et al, 2022). For the decomposition of j e⊥ • E ⊥ , at the later time, the relative importance is consistent with the laminar reconnection studies (e.g., Dahlin et al, 2014Dahlin et al, , 2015Dahlin et al, , 2016Li et al, 2015Li et al, , 2017: the Fermi term (Figure 6c) dominates the positive contribution, and the Betatron term (Figure 6d) is negative.…”
Section: Electron Energizationsupporting
confidence: 88%
“…The contribution by E || (Figure 6b) has a slight decreasing trend over time, where the median value is above 50% at the early time and below 50% later. The dominant role of E || energization is consistent with recent observations in magnetosheath turbulence where the pdf of the work done by E || to electrons is found (Xu et al, 2023), and kinetic simulations of turbulence where T e|| enhancements are found to be significant around the reconnection onset (Franci et al, 2022). For the decomposition of j e⊥ • E ⊥ , at the later time, the relative importance is consistent with the laminar reconnection studies (e.g., Dahlin et al, 2014Dahlin et al, , 2015Dahlin et al, , 2016Li et al, 2015Li et al, , 2017: the Fermi term (Figure 6c) dominates the positive contribution, and the Betatron term (Figure 6d) is negative.…”
Section: Electron Energizationsupporting
confidence: 88%
“…We identify three potential mechanisms that could possibly provide external thermal energy sources or sinks to the electrons in the form of nonzero Ξ: turbulent heating, instabilities, and collisions. The turbulent cascade transfers energy from large scales to kinetic scales, where kinetic processes dissipate the energy in the form of heat (Tu & Marsch 1995;Breech et al 2009;Schekochihin et al 2009;Bruno & Carbone 2013;Goldstein et al 2015;Livadiotis 2019;Franci et al 2022). This form of turbulent dissipation leads to an irreversible deposition of thermal energy.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear at what spatial scales the pressure-strain effect acts. Electron and ion energisations are expected to work at very different scales (Franci et al 2022), but comparable scales are observed in some full-particle simulations (Yang et al 2022). It is also unclear what the role of the turbulence anisotropy is (most of the present simulations are two-dimensional) and how it compares to other processes such as Hall coupling (Papini et al 2019(Papini et al , 2021.…”
Section: Introductionmentioning
confidence: 68%